Chitosan-based nanostructured biomaterials: Synthesis, properties, and biomedical applications - Mazhar Ul-Islam; Khulood Fahad Alabbosh; Sehrish Manan; Shaukat Khan; Furqan Ahmad; Muhammad Wajid Ullah (Advanced Industrial and Engineering Polymer Research, 2024)
Chitosan is obtained from chitin, which is abundantly found in crustaceans and obtained through various methods. The demineralization, deproteinization, discoloration, and deacetylation of chitin produce chitosan consisting of d-glucosamine and N-acetyl d-glucosamine units that are linked through β-(1,4)-glycosidic linkages. Chitosan has gained significant attention in the biomedical field due to its unique properties such as abundance, renewability, non-toxic nature, antimicrobial activity, biodegradability, and polyfunctionality. One of its key properties is its antimicrobial activity, which is why it has been heavily utilized in the biomedical field. To provide a comprehensive overview of chitosan, this review discusses its extraction from chitin and its properties based on its source and extraction methods. It also delves into various chemical modifications and nanocomposite development using natural and synthetic materials. The review emphasizes the multitude of properties that make chitosan an excellent choice for a wide range of biomedical applications. It discusses various mechanisms of antibacterial activity and the factors affecting this activity. Additionally, the review highlights biodegradability, hemocompatibility, antioxidant activity, anti-inflammation, and other properties of chitosan that contribute to its suitability for different biomedical applications, including wound dressing materials, drug delivery carriers, biosensing and diagnostic devices, bone substitutes, and bioimaging. While discussing some limitations of chitosan, the review concludes with an overview of the future perspective for developing multifunctional chitosan-based nanomaterials that could potentially move from laboratory to clinical trials for treating various diseases.